The Application of the Story Teaching Method in Teaching Chinese as a Second Language—Case TCM Allusions - He, Ying; Zhou, Yanhong (Journal of Educational Research and Policies, 2024)
As a special carrier of TCM culture, TCM allusions embody the unique diagnosis and treatment wisdom of TCM, the noble moral sentiments of TCM practitioners and profoundly reflect the essence of Chinese culture. In the teaching of Chinese as a foreign language, TCM allusion can be used as a kind of teaching resource, which can help international students deeply understand TCM and Chinese culture, while improving their Chinese ability and stimulating their enthusiasm for learning. In the creative practice of classroom teaching, teachers cleverly introduce TCM allusions into classroom teaching through the Story Teaching Method. By taking the story as the main line, Chinese knowledge and TCM culture are organically combined, interlocking and fascinating. It can greatly improve the efficiency and interestingness of classroom teaching.